The Works of Lucian of Samosata $1 (BVolume 03s - Lucian, of Samosata, 120-180; Fowler, F. G. (Francis George), 1870-1918; Fowler, H. W. (Henry Watson), 1858-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Works of Lucian of Samosata $1 (BVolume 03" by Lucian of Samosata is a collection of philosophical dialogues and prose written in the early 2nd century AD. The volume explores themes such as friendship, the philosophy of life, and cultural reflections of the time, primarily centering around the character of Demonax, a philosopher hailed for his wisdom and wit. The beginning of this volume introduces Demonax through a rich narrative depicting his life, character, and philosophical insights. It illustrates his disdain for material wealth and social status, emphasizing his commitment to a life of integrity and wisdom. The text highlights anecdotes showcasing his interactions with society and his ability to counsel and reconcile friends in distress, establishing Demonax as a universal figure of kindness and philosophical clarity. The opening concludes with an array of vivid illustrations of his character, setting the stage for deeper philosophical discourses that follow in later sections of the volume. (This is an automatically generated summary.)s
Release date is 2004-11-01
Produced by Robert Nield, Tom Allen, Charles Franks and the Online Distributed Proofreading Team.
Keywords: Lucian, of Samosata -- Translations into English